Morphological and Anatomical Characterization of Ecotype Needles of Cedrus atlantica in Morocco - Nezha El Bakkali; Mohammed Bendriss Amraoui (International Journal of Forestry Research)
Atlas cedar (Cedrus atlantica (Endl.) G. Manetti ex Carrière) is an endemic species in the mountains of North Africa that is attracting international interest in its use in the reforestation of degraded ecosystems. This study aims to investigate and evaluate the morphoanatomical characteristics of needles of four cedar populations localized in the Middle and High Atlas Mountains. Descriptive statistics, analysis of variance (ANOVA), descriptive power, scatter-plot of the discrimination function, scatter-plot of discrimination, and dendrogram of the closest Euclidean distances were made on traits. The results of the linear model of ANOVA nested as population and tree within population suggest the differences statistically significant for the traits measured at a different level. Among these traits, the length of the needle, the width of a vascular bundle including endodermis, and thickness of the wall of hypodermis cell revealed the highest discriminating characters among populations of C. atlantica from the Middle and High Atlas and between the populations of the Middle Atlas. The agglomeration of populations over short Euclidean distances also showed a higher level of differentiation between two ecotypes of C. atlantica not very geographically distant in the Atlas Mountains of Morocco. The ecotype belonging to Aït Oufella and Aït Ayach confers this species a place of choice in the projects of revalorization of the Mediterranean populations, especially in semiarid areas.